Reflection on Technology and Work Life Boundaries - Alwis, S.D. (NSBM Green University, 2019)
This review paper focused on current discussion on technology and work life boundaries. Contemporary workplaces are filled with technology based communication devices such as smartphones connects employees with the organization anytime, anyplace, anywhere. In the light of such development work home boundaries have become blurred and more challenging to maintain. This paper discusses the theoretical underpinnings of work home boundary theory and how they are challenged by new developments in technology intense workplaces.
Keywords: work life boundaries; boundary management; technology; work life conflict